Veterans With Avascular Lower Limb Amputation: Exploring Dual Tasking, Falls, & Instrumental Activities of Daily Living...American Occupational Therapy Association (AOTA INSPIRE) Annual Conference & Expo, March 21-23, 2024, Orlando, Florida. - Swink, Laura A.; Nearing, Kathryn A.; Juarez-Colunga, Elizabeth A.; Schmid, Arlene; Plummer, Prudence; Christiansen, Cory L. (American Journal of Occupational Therapy)
Date Presented 03/23/24 Adults with dysvascular lower limb amputation fell into mutual interference or cognitive priority trade-off groups when going from single to dual tasking. There were no significant differences between repeated-fall (n = 15) and nonfall (n = 10) groups. Primary Author and Speaker: Laura A. Swink Contributing Authors: Kathryn A. Nearing, Elizabeth A. Juarez-Colunga, Arlene Schmid, Prudence Plummer, Cory L. Christiansen